An assessment of the objectives of decentralization in Aceh autonomous region - Razi, Muhammad; Mokhtar, Khairil Azmin (2019)
After about two decades decentralization gained momentum in Aceh it is timely to assess to what extent the aims and objectives of the decentralization have been achieved. This research paper initially seeks to determine the underlying factors and causes of the decentralization in Aceh Special Region. The relationship between the factors and reasons and the objectives and aspirations of the decentralization shall provide clear overall framework of what expected outcome of the whole process. The following part of the paper observes what are taking place in Aceh in relation to the aims and objectives. This would allow an assessment as to what extent the decentralization has achieved its objectives. The research paper would also take note and highlight the challenges and obstacles in achieving the process. This is a qualitative study based on library and internet research. It is also a legal research whereby the relevant laws and constitutional provisions are examined. The data and legal authorities are analyzed accordingly. The study shows that the objectives of decentralization are not fully achieved. However, the agreement which gives autonomy to Aceh has contributed to peace and order to the region. It also accommodates the distinct identity of the Acehnese and provides limited political power to Aceh Government.